Integrated process development: The key to improve Fab production in E. coli. Issue 6 (1st March 2021) - Fink, Mathias; Schimek, Clemens; Cserjan‐Puschmann, Monika; Reinisch, Daniela; Brocard, Cécile; Hahn, Rainer; Striedner, Gerald
Abstract: Bioprocess development and optimization is a challenging, costly, and time‐consuming effort. In this multidisciplinary task, upstream processing (USP) and downstream processing (DSP) are conventionally considered distinct disciplines. This consideration fosters "one‐way" optimization disregarding interdependencies between unit operations; thus, the full potential of the process chain cannot be achieved. Therefore, it is necessary to fully integrate USP and DSP process development to provide balanced biotechnological production processes. The aim of the present study was to investigate how different host/secretory signal/antigen binding fragment (Fab) combinations in E. coli expression systems influence USP, primary recovery performance and the final product quality. We ran identical fed‐batch cultivations with 16 different expression clones to study growth and product formation kinetics, as well as centrifugation efficiency, viscosity, extracellular DNA, and endotoxin content, important parameters in DSP. We observed a severe influence on cell growth, product titer, extracellular product, and cell lysis, accompanied by a significant impact on the analyzed parameters of DSP performance. Our results provide the basis for future research on integrated process development considering interdependencies between USP and DSP; however, individual products need to be considered specifically. These interdependencies need to be understood for rational decision‐making and efficient process development in research and industry. Abstract : The combination of different E. coli hosts, expressed Fabs, and signal sequences used affects upstream processing (USP) in terms of cellular fitness, product titer, and cell broth properties. Consequently, the early stage downstream processing (DSP) unit operations are strongly affected, highlighting the interdependencies of these two disciplines. Therefore, the classical approach to process development, where these are considered separately, needs to be reconsidered and replaced by a holistic and integrated process development in order to fully exploit the potential of the production processes.